For the geometric sequence with tn = 2(-1)^n*(1/3)^n(adsbygoogle = window.adsbygoogle || []).push({});

(a) the sum of the first 99 terms

(b) the sum of the odd-numbered terms t1 + t3 + t5 +...+ t99

(c) the sum of the even-numbered terms t2 + t4 + t6 +...+ t98

so do i first maybe want to convert that into something simpler? why would they write it like that in the first place. a = -2/3, r = -1/3 so wouldnt

tn = (-2/3)(-1/3)^(n-1)?

anyways, after doing that, should i turn that equation into Sn = ?

how would i do b) and c)?

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Sequences series math help

**Physics Forums | Science Articles, Homework Help, Discussion**